Effect of altitude on ticagrelor-induced dyspnea in patients with acute coronary syndrome. Issue 4 (April 2023) - Kocabay, Gonenc; Kivrak, Tarik; Karaca, Ozkan; Karasu, Mehdi; Kaya, Hakki; Kanar, Batur; Orscelik, Ozcan; Kobat, Mehmet Ali; Yilmaz, Mehmet Birhan
Objective: This study aimed to define the association between altitude and ticagrelor-associated dyspnea in patients with acute coronary syndrome (ACS). Methods: We studied consecutive patients with de novo ACS who were admitted to two centers at a low altitude (18 and 25 m, n = 65) and two centers at a high altitude (1313 and 1041 m, n = 136). We managed them with ticagrelor between May 2017 and September 2017. Patients with ACS underwent an interventional procedure within <90 minutes in those with ST elevation and within <3 hours in those without ST elevation. We recorded the incidence of dyspnea in patients with ACS receiving ticagrelor therapy. Results: The mean age was 59.5 ± 10 years, and the mean ejection fraction was 43% ± 18%. A total of 110 (56.7%) patients had ST elevation and 84 (43.3%) did not. There were no significant differences in cardiac risk factors, concurrent medications, or procedural variables between the two groups. Dyspnea developed during hospitalization in 53 (38%) patients from high-altitude centers and in 13 (20%) patients from low-altitude centers (66 patients represented 32% of the total ACS cohort). Conclusions: Dyspnea is a common multifactorial symptom in patients following development of ACS. Ticagrelor-induced dyspnea appears to be associated with altitude.